Students enabling students in a Student Partnership Project : A case study emerging from the OLT Transforming Practice Project on Student Partnerships. - Kek, Megan; Kimmins, Lindy; Lawrence, Jill; Abawi, Lindy; Lindgren, Courtney; Stokes, Trent (Student Success v.8 n.2 p.117-122 https://doi.org/10.5204/ssj.v8i2.389, 2017)
This emerging initiative stemmed from an Office for Learning and Teaching Project (OLT) project, Transforming Practice Programme 2016: Student Engagement: Students as Partners in Teaching and Learning. The initiative, trialed in semester two, 2016, involved the selection and training of two experienced students to be leaders of a Closed Facebook 'students-only' community which provided advice and triaged queries to appropriate channels. The evaluative processes comprised a participatory action research methodology. Two student leaders who facilitated the Closed Facebook and four academic staff of the project were the participants. The findings demonstrate that the Closed Facebook students-only site provided a safe space, outside the formal learning/classroom environment, where student participants were able to ask and share knowledge. The informal student-for-student learning community complemented the formal structure by facilitating the opportunity for students to become 'experts' as university students as they move-through their learning journey. [Author abstract]